Philological Analysis of the Sundanese Folklore 'Lutung Kasarung’ - Heny Subandiyah; Haris Supratno; Resdianto Permata; Fahri Fahri; Fithriyah Inda Nur Abida (Universitas Pendidikan Mandalika, 2023)
One of the most well-known and beloved Sundanese folklore stories is the